Do Discounts and Free Shipping Drive Online Purchase Decisions? Insights from Generation Z E-Commerce Consumers - Iskananda Relian Santri (CV. Visionary Raya Sakti, 2026)
Purpose: This study aims to examine whether price promotion strategies—specifically discounts and free shipping—significantly influence online purchase decisions among Generation Z consumers in the Indonesian e-commerce context. Design/methodology/approach: A quantitative research design was employed using a survey method. Data were collected through an online questionnaire distributed to 120 respondents aged 18–25 who actively shop on Shopee. The sampling technique applied was purposive sampling. Multiple linear regression analysis was conducted using SPSS 25 to test the proposed hypotheses. Findings: The results reveal that both discounts and free shipping have a positive and significant effect on online purchase decisions. Free shipping emerges as the more dominant factor, as it is perceived to provide greater economic value and reduce transaction-related cost concerns among Generation Z consumers. Research implications: The findings reinforce consumer behavior theory by highlighting the critical role of price-related incentives and transaction convenience in shaping purchasing decisions in the digital marketplace. Practically, the study suggests that e-commerce platforms should strategically prioritize free shipping programs alongside discount promotions to effectively attract and retain young consumers in highly competitive online markets.